SYSTEM OF CONCEPTS COMMUNICATIONS OF STATE INSTITUTIONS AND SOCIETY AS THE BASIS OF NATIONAL SECURITY AND SOCIO-ECONOMIC STABILITY - V. Beglytsia; L. Antonova; L. Kozlova; O. Datsii; N. Datsii (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The article analyzes the process of communication between state institutions and society. The study found that all aspects of communication between government institutions and society today acquire the characteristics of digital communication. This means that for the process of communication between government and society, its interactivity, multimedia, efficiency, extraterritoriality become relevant. It is also characteristic that the communication of state institutions and society acquires certain systemic properties — emergence, inherence, integrity. Also, as a result of the analytical study, there is a significant disparity in the access of different groups of the population to modern information and communication technologies and, as a consequence, the formation of different levels of their uptake by these groups of the population. Therefore, to increase the efficiency of communications, the subjects of the communication process should use a system of different channels of information transmission and use not a single concept, but a system of communication concepts to ensure national security and socio-economic stability. It is proven that the basis and guarantee of the formation and introduction of a systematic conceptual approach to the practical application of information and communication technologies of state institutions and society is the inevitable end-to-end digitalization of Ukraine. The process of digitalization will lead to a change in social and political activities of citizens, the formation of social strata, which is the germ of the information society and will require intellectual communication. The existence of a system of communication concepts has led to the use of a systematic approach to create an algorithm for the formation and implementation of effective communications of state institutions and society. The complex of requirements to the specified system of communications is formed due to the research. This system should be aimed at reconciling and harmonizing the interests and positions of communities of citizens; integration of social communities, optimization of administrative activity based on democratic values and observance of citizens’ rights. It also proposes areas of work to fulfill the tasks facing state institutions and society to harmonize the information and communication process and to form the basis of social stability and guarantee national security.